Corporate Social Responsibility Research in Accounting: Evidence from Turkey - Ümmühan Aslan; Seçil Sigalı (Journal of Accounting and Management Information Systems (JAMIS), 2016)
The aim of this study is to examine the corporate social responsibility (CSR) practices and reporting in Turkey, as reflected by the accounting research. Research findings are examined and classified in two main approaches, which are "CSR Awareness" and "Determinants and Impacts of CSR Practices and Reporting". The findings show that the external incentives are insufficient in promoting CSR practices in Turkey. Research calls for more enforcement, specifically related to the environmental disclosures. Although the findings on the bidirectional relationship between CSR practices and the financial performance variables are contradictory, company size and growth, sound corporate governance practices as board independency is found as significant determinants of the extent of the CSR disclosures.
Keywords: M41; M14; 650; Corporate Social Responsibility; Accounting Research; Turkey